Deriving market prices for forestland properties from comparables. Issue 4 (27th July 2018) - Eerikäinen, Kalle; Venho, Mika
Abstract : Purpose: The purpose of this paper is to construct a market price predictor (MPP) for forestland properties by applying a sales comparison approach (SCA) with several value-related characteristics obtainable from the property-specific sales line declarations. Design/methodology/approach: An SCA-based predictor was designed for appraising and valuing forestland properties with varying quantitative features that impact their overall value. Using a two-stage classification procedure, representative reference sales (i.e. comparables) are objectively and commensurately selected for the subject using location and forest characteristics as classifiers. Findings: The new SCA-based MPP is a stable and reliable tool applicable for pricing forestland properties in any location when data from comparables are available. Research limitations/implications: A systematic and spatio-temporally continuous data collection procedure is a prerequisite for obtaining appropriate data for the SCA-based appraisal and valuation techniques, including the MPP model presented in this study. Practical implications: The MPP model is suitable for the practical appraisal and valuation of forestland properties. Social implications: It is expected that by applying the MPP model for the appraisal and valuation of forestland properties, positive societal contributions will be achieved through the intensification of the forestland property market. Originality/value: The MPP model provides an objective alternative to the adding-value technique, which is the most commonly applied tool to appraise forestland properties in Finland. It is also offers an assumption-free alternative to the income approach.